Level and determinants of pregnancy care in developing countries: the case of Bangladesh, 1999 - 2000 - Ahmed, Syed Masud; Mahbub, Amina (BRAC Research and Evaluation Division (RED), 2019)
This study explored the current state of pregnancy care in Bangladesh using data from the Bangladesh Demographic and Health survey (1999-2000), based on a nation-wide representative sample. Data were collected from women with reference to the most recent live birth occurring in the preceding five years. Findings revealed that 72% of the pregnant women did not have any ANC visit while only 8% completed 4 visits. Of those who visited, 77% were attended by health professionals (doctors, nurses, mid-wives). Most of the deliveries (92%) took place at home while only 4% took place in govt. health facilities. Untrained TBAs delivered more than half of the babies while only 7% of the deliveries were attended by qualified medical practitioners and 22% by relatives or other non-professionals. Deliveries by health professionals increased from 10% in 1993-94 to 14% in 1999-2000 (p<O.OOI), due largely to increase in the proportion of delivery attended by doctors from 4.4% to 8.8% during this period. Logistic regression identified mother's age, education, religion, residence, ANC visits and wealth quintiles to be important predictors of the presence of skilled attendants at delivery. The programme implications of these findings are discussed.